2017
DOI: 10.1371/journal.pgen.1007150
|View full text |Cite
|
Sign up to set email alerts
|

Loss-of-function of the ciliopathy protein Cc2d2a disorganizes the vesicle fusion machinery at the periciliary membrane and indirectly affects Rab8-trafficking in zebrafish photoreceptors

Abstract: Ciliopathies are human disorders caused by dysfunction of primary cilia, ubiquitous organelles involved in transduction of environmental signals such as light sensation in photoreceptors. Concentration of signal detection proteins such as opsins in the ciliary membrane is achieved by RabGTPase-regulated polarized vesicle trafficking and by a selective barrier at the ciliary base, the transition zone (TZ). Dysfunction of the TZ protein CC2D2A causes Joubert/Meckel syndromes in humans and loss of ciliary protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 73 publications
2
33
0
Order By: Relevance
“…This unexpected finding suggests either species differences between mouse and frog or indicates very high redundancy between Rabs. Our recent work in zebrafish supports a role for Rab8 in Rhodopsin trafficking: We confirmed the presence of Rab8 at the surface of OCVs using correlative light and electron microscopy and observed Rab8-positive particles moving along with Rhodopsin in the IS region with live imaging (Figure 2) [23].…”
Section: The Road To the Outer Segment -Trafficking Towards The Ciliumsupporting
confidence: 73%
See 1 more Smart Citation
“…This unexpected finding suggests either species differences between mouse and frog or indicates very high redundancy between Rabs. Our recent work in zebrafish supports a role for Rab8 in Rhodopsin trafficking: We confirmed the presence of Rab8 at the surface of OCVs using correlative light and electron microscopy and observed Rab8-positive particles moving along with Rhodopsin in the IS region with live imaging (Figure 2) [23].…”
Section: The Road To the Outer Segment -Trafficking Towards The Ciliumsupporting
confidence: 73%
“…and Syntaxin3 [23,26,27], explaining the observed massive accumulation of unfused vesicles in cc2d2a-/-zebrafish PRs.…”
Section: The Connecting Cilium-at the Crossroads Between Inner And Oumentioning
confidence: 89%
“…Rhodopsin uptake into Golgi-to-ciliadirected rhodopsin transport carriers (RTCs) is linked with the recruitment and activation of fusion regulators through the wellconserved ciliary trafficking network mediated by Arf4 binding the VxPx motif in rhodopsin (Ezratty et al, 2016;Wang and Deretic, 2014;Ward et al, 2011). The Arf4-based ciliary targeting complex is composed of, and is sequentially ordered by, the Arf GAP ASAP1 (Brown et al, 1998), a GAP and an effector of Arf4, and the Rab11-FIP3-Rabin8 dual effector complex, which ultimately activates Rab8, a regulator of carrier fusion with the periciliary plasma membrane (note that Rab8 and Rab11 both have a and b forms, Rabin8 is also known as RAB3IP, and FIP3 is also known as RAB11FIP3) (Bachmann-Gagescu et al, 2011;Deretic et al, 1995;Mazelova et al, 2009a;Moritz et al, 2001;Ojeda Naharros et al, 2017;Omori et al, 2008;Vetter et al, 2015a,b;Wang and Deretic, 2015;Wang et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Rab8-coated vesicles accumulated at the apical inner segments suggesting CC2D2A is important for membrane protein trafficking in zebrafish (Bachmann-Gagescu et al, 2012; Mougou-Zerelli et al, 2009). Ojeda Naharros, et al, showed recently that CC2D2A plays a role in the docking of opsin-laden vesicles at the periciliary membrane (Ojeda Naharros et al, 2017). By contrast, the Cc2d2a −/− mouse recapitulates features of Meckel syndrome with multiorgan defects (Veleri et al, 2014).…”
Section: Centriole and Pcm Componentsmentioning
confidence: 99%